USING EXELSA MOODLE TO DEVELOP MATHEMATICS TEACHING SKILLS AND SPIRIT IN THE MICRO TEACHING COURSE - Rudhito, Marcellinus Andy (Sanata Dharma University Yogyakarta, 2018)
The purpose of learning implementation with the development of digital learning resources in the Micro Teaching Course is to (i) design and implement active and constructive learning dynamics in an effort to develop students' Ignatian Pedagogy-based teaching skills by utilizing Learning Management System Exelsa Moodle; (ii) produce teaching design and teaching videos that students can use in their efforts to develop their teaching skills. In general, the implementation of learning is about 90% in accordance with the plan. The expected final achievement is generally achieved, namely that students have good skills in managing mathematics learning in the peer teaching (Competence), have high spirit in developing teaching ability (Conscience) and have high concern in helping their friends in an effort to develop their teaching skills (Compassion).The use of Exelsa Moodle is also quite optimal, in which the course design and explanations and materials used in the lectures can be well communicated. Videos from short film projects with mathematical themes can also be produced properly and have been uploaded on Youtube. In this lecture the videos recording their teaching practice still tend to be a collection of learning and student labs concerned. These videos can be utilized to serve as examples in the discussion of teaching skills, whether from material mastery, delivery or class management.Â DOI: https://doi.org/10.24071/ijiet.2018.020210